Leadership and Followership in Health Professions: A Systematic Review - Patrick Gallegos; Muhammad Salaar Riaz; Michael Peeters (University of Minnesota Libraries Publishing, 2024)
Objective: Leadership discussion, including leadership development programs, is common. However, discussion of followership as a component of leadership seems less frequently discussed. With a focus on leadership and followership, this investigation reviewed the health-professions education literature and characterized leadership-followership within health-professions education. Methods: Using PubMed, ERIC, and Google Scholar, two investigators independently and systematically searched health-professions education literature for articles related to leadership and followership. Reports were categorized based on the articles by type, application, profession, leadership, and followership qualities. Results: Eighty-one articles were included. More than half (48/81, 59%) were theoretical, 27% (22/81) empirical, 7% (6/81) commentaries, and 6% (5/81) letters-to-the-editor). Empirical studies did not share outcomes that could be meaningfully combined quantitatively by meta-analysis; however, the vast majority (96%) of theoretical articles discussed a healthcare-related application of leadership and followership (e.g., improving patient care, improving communication, improving organizational efficiency). Thus, a qualitative review was completed. Of the 81 articles, 57% (n=46) involved multiple professions, while 43% (n=35) focused on a specific profession [Nursing (n=16), Medicine (n=7), Others (n=5) Surgery (n=3), Pharmacy (n=2), Veterinary Medicine (n=2)]. While most articles (75%) discussed leadership qualities (with top qualities of effective communication, visionary, and delegating tasks), fewer (57%) discussed followership qualities (with top qualities of being responsible, committed, and supportive). Of note, some qualities overlapped in both leadership and followership (with top qualities of effective communication, being supportive, and providing/receiving feedback). Conclusions: Leadership-Followership was described in many health-professions' education literature. However, Pharmacy and Veterinary Medicine had substantially fewer articles published on this topic. Notably, followership did not receive nearly as much attention as leadership. Leadership has a dynamic and complex interaction with followership highlighting that an effective leader must know how to be an effective follower and vice versa. To improve leadership within healthcare teamwork, education should focus on both leadership-followership.